The Impact of Artificial Intelligence on Students Across Generations in Nigeria: A Review - Odili, David; Ebiye, Margaret (Kashere Journal of Education, 2025)
Artificial Intelligence (AI) is reshaping learning across Nigeria, influencing children, adolescents, university students, and adults. While traditional and early digital learning relied on textbooks, chalkboards, and manual research, AI-driven tools now provide personalised learning, instant information access, improved comprehension, and support for students with diverse needs. Studies show that Nigerian students frequently use tools such as ChatGPT, Grammarly, and adaptive learning platforms, reporting enhanced academic performance, faster task completion, and increased engagement. Educators also acknowledge AI’s value in assessment, accessibility, and instructional support. Despite these advantages, significant risks exist. Overreliance on AI reduces critical thinking, creativity, and deep learning. Academic dishonesty, misinformation, data privacy concerns, infrastructural limitations, and unequal access remain major challenges. There are also fears of cultural erosion and teacher displacement. To ensure balanced integration, Nigeria must strengthen digital literacy, teacher training, ethical guidelines, and policy frameworks so that AI complements—rather than replaces—human intelligence and educational values.